The Effect of Work-Family Conflict and Family-Work Conflict on Performance with Work-Life-Balance as an Intervening Variable - Dimas Putra Sampurna; Suharnomo Suharnomo (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
A person is currently facing problems such as conflict between work to family and family to work. Therefore, the purpose of this paper is to explore the relationship between work-family conflict and family-work conflict and employee performance with work-life balance as a moderating variable. The object of this research is a full-time teaching lecturer. With 105 teaching staff at Muhammadiyah University in Lamongan as respondents, they applied linear regression analysis to test seven hypotheses. The results of the study show that work-family conflict and family-work conflict have a positive effect on employee performance. Work-life balance has a moderating effect on the relationship between family-work conflict and employee performance.